Prospective, non-interventional, multicenter study of the intraocular pressure-lowering effects of prostaglandin analog/prostamide-containing therapies in previously treated patients with open-angle glaucoma or ocular hypertension - (:unkn) unknown (DOVE MEDICAL PRESS LTD, 2017)
Objective: The objective of this study was to assess the intraocular pressure (IOP)-lowering efficacy, tolerability, safety, and usage patterns of prostaglandin analog/prostamide (PGA/P)containing topical ocular hypotensives in ocular hypertension (OHT) and primary open-angle glaucoma in the Turkish clinical setting. Methods: This non-interventional, multicenter study enrolled previously treated patients who failed to achieve target IOP (or experienced unacceptable adverse events [AEs]) and were prescribed a PGA/P-containing IOP-lowering agent. Treatment was initiated at baseline (V1), and patients returned at weeks 4-6 (V2) and 8-12 (V3). The primary efficacy measure was the change in IOP from baseline at V3 in each eye. The secondary measures were physician's assessment of IOP-lowering efficacy, patients (%) reaching target IOP determined at V1, hyperemia score, physician and patient assessment of study treatment tolerability at V3, and AE frequency/severity. A subgroup analysis of patients receiving the most common study treatment was conducted. All analyses were performed using the safety population (patients who received one or more doses and had any data available). Results: Of 358 enrolled patients, 60.6% had primary open-angle glaucoma, 29.9% had secondary open-angle glaucoma (protocol amendment), and 13.1% had OHT; 13 patients had multiple diagnoses. At V3, the mean IOP change from baseline was >=-4.2 mmHg (>= 21.1%). IOP met or was lower than the target in 81.7% of patients, 95% exhibited none to mild conjunctival hyperemia (most common AE), and tolerability was rated good/very good by.91.1% of patients and physicians. The results were similar in patients who received the most common study treatment, bimatoprost 0.03%/timolol 0.5% (bim/tim; n=310). Conclusion: PGA/P-containing medications, including bim/tim, significantly reduced IOP in previously treated patients with open-angle glaucoma or OHT; most reached their target IOP or an IOP even lower than their target and reported good/very good tolerability. PGA/P-containing medications such as bim/tim should be considered as a safe, effective therapeutic option for Turkish patients who exhibit poor response, tolerance, or adherence to their previous therapy.
Keywords: glaucoma; ocular hypertension; bimatoprost; timolol; prostaglandin analog; prostamide; BIMATOPROST/TIMOLOL FIXED COMBINATION; TIMOLOL MALEATE; PSEUDOEXFOLIATION SYNDROME; INDIVIDUAL COMPONENTS; CHINESE PATIENTS; CLINICAL-TRIAL; PLUS TIMOLOL; LATANOPROST; EFFICACY; SAFETY